2013
DOI: 10.1111/cpf.12108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise intensity on systemic oxidative stress and antioxidant capacity

Abstract: The aim of the current study was to examine the influence of exercise intensity on systemic oxidative stress (OS) and endogenous antioxidant capacity. Non-smoking, sedentary healthy adult males (n = 14) participated in two exercise sessions using an electronically braked cycle ergometer. The first session consisted of a graded exercise test to determine maximal power output and oxygen consumption (VO(2max)). One week later, participants undertook 5-min cycling bouts at 40%, 55%, 70%, 85% and 100% of VO(2max), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 40 publications
4
72
2
3
Order By: Relevance
“…However, the overproduction of ROS induced by exhaustive exercise training or other stresses, along with compromised antioxidant defenses, can lead to oxidative stress and related tissue damage (Powers et al, 2011b; Zuo et al, 2012). Interestingly, proper exercise (moderate to high intensity exercise) stimulates the adaptive responses and strengthens the endogenous antioxidant defense systems to combat excessive ROS thereby maintaining muscle redox balance (Parker et al, 2014; Zuo et al, 2015b). …”
Section: Introductionmentioning
confidence: 99%
“…However, the overproduction of ROS induced by exhaustive exercise training or other stresses, along with compromised antioxidant defenses, can lead to oxidative stress and related tissue damage (Powers et al, 2011b; Zuo et al, 2012). Interestingly, proper exercise (moderate to high intensity exercise) stimulates the adaptive responses and strengthens the endogenous antioxidant defense systems to combat excessive ROS thereby maintaining muscle redox balance (Parker et al, 2014; Zuo et al, 2015b). …”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, the intensity of exercise needed to produce the most favourable changes in redox homeostasis, the balance between RS and antioxidants, is still under debate. 7,8,9 High-intensity interval training (HIIT) is a time efficient way of increasing cardiorespiratory fitness with double the improvements in VO2peak in a shorter exercise time. 10 It has been suggested that HIIT may provide greater improvements in redox homeostasis regulation than traditional moderate-intensity continuous training (MICT).…”
Section: Introductionmentioning
confidence: 99%
“…A single session of low to moderate-intensity exercise in healthy males attenuates the postprandial oxidative stress response to a meal ingested 2 h before (Mc Clean et al, 2007) and 24 h after exercise (Takahashi et al, 2015). Furthermore, high-intensity exercise which elicits greater oxidative stress and antioxidant activity compared to low to moderate intensity exercise (Schneider et al, 2005; Fisher-Wellman and Bloomer, 2009; Parker et al, 2014), may also attenuate postprandial oxidative stress (Tyldum et al, 2009; Gabriel et al, 2012). Considering the impact of HIIE on postprandial oxidative stress are equivocal (Canale et al, 2014), and overweight and inactive population's exhibit greater basal and postprandial oxidative stress than healthy controls (Tucker et al, 2008; Fisher-Wellman et al, 2009), further research is warranted.…”
Section: Introductionmentioning
confidence: 99%